KUALITAS PRODUK, HARGA, PROMOSI, DITRIBUSI, KEPUTUSAN PEMBELIAN: STUDI PADA PRODUK INDOMIE - Prayogo, Rangga Restu; Pramana, Dodi; Azizah, Nurul (Jurnal Bisnis Indonesia, 2019)
One of the companies that produces the largest instant noodles in Indonesia is PT. Indofood CBP Sukses Makmur, Tbk, which produces Indomie. By winning the TOP Brand Award for 2 years, showing the existence of Indomie products. This is inseparable from the company's ability to eliminate the marketing mix, ranging from product quality, price, promotion, and distribution that continues to be developed. The purpose of this study was to analyze the effect of product quality, price, promotion, and distribution simultaneously and partially on consumer decisions in buying Indomie products. This type of research uses descriptive quantitative research with respondents from faculty of economics who have consumed Indomie. The questionnaire was given to 100 respondents with a sampling technique that is purposive sampling. The results showed the product quality, price, promotion, and distribution carried out simultaneously and partially on the consumer's decision to buy Indomie products. Keywords: Product, Price, Promotion, Distribution, Purchase Decision.